2017
DOI: 10.23937/2469-5858/1510029
|View full text |Cite
|
Sign up to set email alerts
|

Association between Extreme Cold Weather Temperatures and Mortality in Greece

Abstract: Background: Little is known about cold-related mortality in south Europe. The aim of this study was to investigate the association between extreme cold weather and mortality in Greece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Indeed, in such a population, physiological heat strain may have serious health consequences ( Kenney et al, 2014 ). Despite several epidemiological studies ( Basu and Samet, 2002 ; Gasparrini et al, 2015 ; Amorim et al, 2017 ; Ioannou et al, 2018 ; Tsoutsoubi et al, 2021 ) investigating this issue, the increased cardiovascular morbidity and mortality, particularly in working populations, remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in such a population, physiological heat strain may have serious health consequences ( Kenney et al, 2014 ). Despite several epidemiological studies ( Basu and Samet, 2002 ; Gasparrini et al, 2015 ; Amorim et al, 2017 ; Ioannou et al, 2018 ; Tsoutsoubi et al, 2021 ) investigating this issue, the increased cardiovascular morbidity and mortality, particularly in working populations, remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the increase in mortality rate during the summer can be as high as 400% [5]. The association between mortality and ambient temperature is cause-specific, as some studies have reported that both cold and hot ambient temperatures increases mortality rates due to cardiovascular causes [1,[5][6][7][8][9][10]. Furthermore, the relationship between ambient temperature and all-cause mortality rate is not the same in all age groups; the daily number of heat-related deaths is more prevalent among elderly individuals [6,11].…”
Section: Introductionmentioning
confidence: 99%